Multicomponent synthesis of some new (1S,4S)-2,5-diazabicyclo[2.2.1]heptane-dithiocarbamates and their in vitro anti-proliferative activity against CaSki, MDA-MB-231 and SK-Lu-1 tumour cells as apoptosis inducing agents without necrosis - Sujay Laskar; Luis Sánchez-Sánchez; Manuel López-Ortiz; Hugo López-Muñoz; María L. Escobar-Sánchez; Arturo T. Sánchez; Ignacio Regla (Taylor & Francis Group, 2017)
Identification of a new class of antitumor agent capable to induce apoptosis without triggering necrotic cell death event is challenging. The present communication describes the multicomponent synthesis of seven new (1S,4S)-2,5-diazabicyclo[2.2.1]heptane-dithiocarbamates and their in vitro antiproliferative activity on cervical cancer cell line (CaSki), breast cancer cell line (MDA-MB231), lung cancer cell line (SK-Lu-1) and human lymphocytes. Among the synthesized dithiocarbamates, compound 9e displayed significant antiproliferative activity without inducing any necrotic cell death (both on tumour cells and lymphocytes) and induced apoptosis in tumor cells by the caspase dependent apoptotic pathway. The compound 9e also exhibited greater tumor selectivity than human lymphocytes. In silico ADME predictions revealed that compound 9e has the potential to be developed as a drug candidate. Rapid chemical modifications of this lead are thus highly necessary for further investigation as a drug like safer antitumor candidate and also to achieve compounds with better activity profile.